KAJIAN PENGEMBANGAN SDM DALAM MENINGKATKAN MOTIVASI DAN DISIPLIN KERJA KARYAWAN DI ERA DIGITAL - Andarbeni, Ninnes Sri; Saputri, Afifah Widiya; Ismail, Iriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine how human resource (HR) development can affect employee motivation and work discipline in the digital era and its impact on employees. The type of research used is a literature study conducted based on theoretical studies from searches of previous research journals, books, and other papers. The results of the study show that HR development in improving work motivation and discipline can be through career development, a fair reward and sanction system, work-life balance, good interpersonal communication which can increase motivation and result in increased performance, and the implementation of HR information systems, online attendance systems can be done to improve employee work discipline in the digital era. The conclusion of the influence of HR development on motivation and work discipline where motivation and work discipline can improve employee performance, the higher the motivation the higher the employee performance and the higher the work discipline the more competent the employee is which makes better performance.